Implementation of Islamic Approach-based Curriculum in Madrasah Ibtidaiyah (MI) Boarding School to Strengthen Students' Religious Character - Bagus Wahyu Setyawan; Chafit Ulya; Sa'adatun Nuril Hidayah; Ku-Ares Tawandorloh (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2023)
Religious character is one of the important characteristics to be developed, especially for students in the era of globalization. In fact, in some educational institutions, there is no particular curriculum to support the purpose of this study to examine in depth the implementation of the Islamic Approach-based curriculum as a medium to strengthen the religious character of Islamic boarding school madrasah ibtidaiyah students. The samples in this study were taken from madrasah ibtidaiyah in Tulungagung and Ponorogo. This research is case study research with data sources in the form of learning processes and informants consisting of students and teachers. Data were collected by observation and in-depth interviews with teachers, ustaz/ustazah, and students. The sample in this study consisted of 5 teachers and 20 students in each school. The results showed that there is a curriculum to develop religious character, discipline, and responsibility. The curriculum in each madrasah ibtidaiyah Boarding School is implemented in programs, both curricular and extracurricular. The integration of the national curriculum with the hidden curriculum in each institution makes the character education process maximized. Implemented programs such as praying before starting learning, saying greetings, and asking for ridho to the teacher/ustaz for religious character development. The habit of arriving on time, cultivating queuing, and utilizing free time to strengthen student discipline. For the development of responsibility, there is a picket program and a reward and punishment system. In addition, there is good coordination between teachers, ustaz, dormitory caregivers, and the foundation in determining effective programs in order to develop student character.